Estudo sobre redes cicloviárias em regiões metropolitanas - Freato, Maria Paula Rosa (2023)
The choice of non-motorized modes of transportation for the population's displacement is essential in order to elevate standards of quality of life. The bicycle, for example, can be an element of reordering and reconfiguration of urban space, as well as efficiently integrating with other modes. Much is discussed nationally and internationally about utilitarian bicycle trips in the urban context. Thus, extrapolating to a regional context, promoting the use of bicycles for daily commuting between cities located in metropolitan regions can be an alternative. Therefore, considering that the strategic planning of cycle networks between cities in the face of Brazilian urban-road interfaces is still incipient, this study sought to study the relationship between cycling and commuting trips through infrastructure evaluation. Thus, the present study aimed to define an evaluation method for a cycle network for commuting trips on a metropolitan scale, considering safety and accessibility criteria. The study was composed of two stages: (1) definition of an instrument for evaluating cycle infrastructure in metropolitan regions through Analytic Hierarchy Process (AHP) analysis and (2) application of the instrument in the case study, using Geographic Information System. For the development of stage 1, a questionnaire was elaborated and applied to obtain a hierarchy of importance among the criteria through the perception of the interviewees. For stage 2, the recent and promising Metropolitan Region of Ribeirão Preto (SP) was chosen as the study area, due to its non-conurban territorial characteristics and presence of intense commuting flows. The results indicated: (i) according to the general perception of the interviewees, the order of importance of the criteria (stage 1), being (a) cycle management (0.29), (b) cycle design (0.28), (c) cycle perception (0.22), (d) cycle facilities (0.21); and (ii) in the case study in RMRP (stage 2), roads with potential for implementing a cycle network that connect Ribeirão Preto to the cities of (a) Jardinópolis, (b) Sertãozinho, (c) Serrana, in addition to its ring road, however, mostly characterized by regular and poor scores. Finally, considering that the selected areas are of great relevance and, on the other hand, present their weaknesses, the suggested network was qualified in order to establish it to local realities. It is concluded that the study contributed to the use of bicycles in medium and long-distance routes, from the perspective of safety, as well as emphasized a great potential for implementing a cycle network in Metropolitan Region of Ribeirão Preto (SP).